BRAF Inhibitor Resistance Confers Increased Sensitivity to Mitotic Inhibitors - Misek, Sean A.; Foda, Bardees M.; Dexheimer, Thomas S.; Akram, Maisah; Conrad, Susan E.; Schmidt, Jens C.; Neubig, Richard R.; Gallo, Kathleen A. (Frontiers in Oncology, 2022)
Single agent and combination therapy with BRAFV600E/K and MEK inhibitors have remarkable efficacy against melanoma tumors with activating BRAF mutations, but in most cases BRAF inhibitor (BRAFi) resistance eventually develops. One resistance mechanism is reactivation of the ERK pathway. However, only about half of BRAFi resistance is due to ERK reactivation. The purpose of this study is to uncover pharmacological vulnerabilities of BRAFi-resistant melanoma cells, with the goal of identifying new therapeutic options for patients whose tumors have developed resistance to BRAFi/MEKi therapy. We screened a well-annotated compound library against a panel of isogenic pairs of parental and BRAFi-resistant melanoma cell lines to identify classes of compounds that selectively target BRAFi-resistant cells over their BRAFi-sensitive counterparts. Two distinct patterns of increased sensitivity to classes of pharmacological inhibitors emerged. In two cell line pairs, BRAFi resistance conferred increased sensitivity to compounds that share the property of cell cycle arrest at M-phase, including inhibitors of aurora kinase (AURK), polo-like kinase (PLK), tubulin, and kinesin. Live cell microscopy, used to track mitosis in real time, revealed that parental but not BRAFi-resistant melanoma cells were able to exit from compound-induced mitotic arrest through mitotic slippage, thus escaping death. Consistent with the key role of Cyclin B1 levels to regulate mitosis at the spindle checkpoint in arrested cells, we found lower Cyclin B1 levels in parental vs. BRAFi-resistant melanoma cells, suggesting that inability to down-regulate Cyclin B1 expression levels may explain the increased vulnerability of resistant cells to mitotic inhibitors. Another BRAFi-resistant cell line showed increased sensitivity to Chk1/2 inhibitors, possibly due to an accumulation of DNA damage, resulting in mitotic failure. This study demonstrates that BRAFi-resistance, in at least a subset of melanoma cells, confers vulnerability to pharmacological disruption of mitosis and suggests a targeted synthetic lethal approach for overcoming resistance to BRAF/MEK-directed therapies.